Hepatoprotective effect of Artichoke (Cynara scolymus) in laying hens - Ürüşan, H (Journal of the Hellenic Veterinary Medical Society, 2023)
This experiment was conducted to investigate the effect of artichoke plant (Cynara scolymus) at different ratios (0, 5, 10 and 15 g/kg) supplementation into high-energy laying hen diet on performance, egg quality parameters, serum lipid profile, some liver enzymes and liver fat ratio. In total, one hundred and twenty 70-week-old Lohman LSL laying hens were randomly assigned to five groups and each group consisted of six subgroups. The control group was fed the basal feed (2650 kcal/kg ME), and the treatments groups were fed with high energy (2850 kcal/kg ME) including 0, 5, 10 and 15 g/kg artichoke, respectively. The feed and water were given to animals as ad-libitum during the experimental period. Experiment lasted for 8 weeks. The supplementation of 10 g/kg artichoke to the diet improved feed conversion ratio (FCR) and increased egg production. All additive artichoke diets showed the highest eggshell weight, shell breaking strength, shell thickness and yolk color. The addition of artichoke to the high energy diet reduced the serum triglyceride, LDL and VLDL concentration. The GSH, CAT and GPx values which are enzymatic antioxidants in serum were found to be highest in the HE+ artichoke 5 g/kg group. The liver fat content was dramatically lower in laying hens fed on HE+artichoke 10 g/kg diet (18.83 %) compared with those fed on the high energy diet (48.26 %). As s result, dietary supplementation of artichoke could be used in the diets to improve the performance, shell weight, breaking strength, thickness of shell, egg yolk color and reduced to serum triglyceride, LDL and VLDL concentration, liver fat ratio and increased the serum antioxidants enzymes (GSH, CAT and GPx).